Surface modification of recycled coir fibers with hybrid coating and its effect on the properties of ABS composites - Jiafeng Cai; Qiuying Li; Chifei Wu (Materials Research Express, 2022)
In this work, a hybrid coating (TSMA) was produced using tetraethyl orthosilicate (TEOS)/KH550/Styrene maleic anhydride copolymer (SMA) as raw materials. The coating was afterwards applied to modify recycled coir (r-coir) fibers via dip-coating. R-coir fibers reinforced ABS composites were then prepared and the reinforcing effect of fibers on the composite structure was investigated, as well. The r-coir fibers coated with TSMA were hydrolyzed in air for 3 days. The SiO _2 particles produced by sol-gel reaction of TEOS were used to connect KH550 and SMA to the surface of the fibers and form an organic-inorganic ‘armor’ structure. The successful surface modification of the r-coir fibers was proved via FTIR spectroscopic study and the improvement of their decomposition temperature was evidenced by TGA. Furthermore, the homogeneous dispersion of TSMA on the surface of r-coir fibers was observed via SEM. In addition, the tensile strength of single fibers was found to increase by 36.1%. According to the results, TSMA can be successfully homogenized on the fiber surface, enabling one to repair the damaged areas and improve the tensile strength of single fibers. Besides, good compatibility between r-coir fibers and ABS was revealed by contact angle measurements. Furthermore, the bending strength and elastic modulus of TSMA-modified r-coir fibers/ABS composites were improved by 6% and 27%, respectively. Therefore, the method of plant fiber modification proposed in present work provides a reliable way for effective reuse of r-coir fibers.